How can UK Housing Projects be Brought in Line With Net-Zero Carbon Emission Targets? - Jankovic, Ljubomir; Bharadwaj, Purvesh; Carta, Silvio (Frontiers in Built Environment, 2021)
Numerous local authorities are committed to constructing buildings to net-zero carbon emissions performance, and have declared carbon emergency, striving to reach carbon neutrality well before 2050. However, buildings in the UK are currently being designed and constructed to current building regulations which do not require net-zero performance, and these buildings will last well beyond 2050. This paper presents a case study of a housing development in Hertfordshire, UK, where a structured approach for achieving net-zero carbon performance homes was developed. The methodology was based on dynamic simulation to design net-zero emissions from building operation, and an industry standard inventory of carbon and energy database was used to evaluate embodied emissions in building materials. The approach comprised of developing dynamic simulation models to investigate the improvement in energy performance of the development through fabric-first approach, focusing on building envelope design prior introducing renewable energy systems, in order to achieve operational net-zero carbon performance. Carbon emissions (operational and embodied) were investigated to assess the appropriateness of the deployed strategies. Dynamic simulation results combined with embodied emissions analysis illustrated that, by combining embodied and operational emissions, a net-zero carbon performance would be achievable by the 2050 target only if alternative building materials based on photosynthetic bio-composites are used. This analysis also highlighted the limitations of conventional retrofit interventions carried out ten years after the construction as they resulted in increased embodied carbon emissions, thus lengthening the time period well beyond the 2050 target for achieving net-zero carbon performance. As the use of conventional materials appeared to delay the achievement of net-zero emissions by several decades, the only way to achieve net-zero targets before 2050 is to design new buildings to be carbon negative from the operational point of view and to use photosynthetic materials for their construction.